2017
DOI: 10.1016/j.clnesp.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Removal of percutaneous endoscopic gastrostomy tubes in adults using the “cut and push” method: A systematic review

Abstract: The quality and quantity of the evidence on CP is insufficient to make recommendations for clinical practice. Further research is needed to evaluate the effectiveness of CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This is particularly useful for patients with a D-PEJ, in whom endoscopic retrieval can be particularly challenging and invasive [36]. Endoscopic retrieval of the bumper is recommended in cases with previous bowel surgery and for patients at risk of strictures or ileus, which could hinder spontaneous migration and elimination of the tube remnant and bumper [1,157,158].…”
Section: Definitive Enteral Tube Removalmentioning
confidence: 99%
“…This is particularly useful for patients with a D-PEJ, in whom endoscopic retrieval can be particularly challenging and invasive [36]. Endoscopic retrieval of the bumper is recommended in cases with previous bowel surgery and for patients at risk of strictures or ileus, which could hinder spontaneous migration and elimination of the tube remnant and bumper [1,157,158].…”
Section: Definitive Enteral Tube Removalmentioning
confidence: 99%
“…This suggests complications following C&P are uncommon. In a systematic review including 5 cohort studies and 22 case studies with a total of 373 cases of C&P, a complication rate of less than 1% was identified [ 1 ]. The most frequent complication was gastrointestinal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent complication was gastrointestinal obstruction. While often resolving spontaneously, these complications sometimes require intervention such as laparotomy or endoscopy [ 1 ]. A small number of case studies report significant complications following C&P in adults including peritonitis, bleeding and even mortality [ 9 – 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations